Strengthening the competitiveness of Islamic boarding schools: Strategic insights from a pondok pesantren - Tristianingrum, Indah; Nugroho, Aris Dwi; Fitriani, Suci (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the strategic development of Pondok Pesantren Ash-Shiddiiqi in strengthening institutional competitiveness within contemporary educational contexts. Using a qualitative case study design, data were collected through interviews with institutional leaders, teachers, and students. The findings reveal four key strategic dimensions: the integration of digital technology into learning, the balance between religious and general education, community and alumni engagement, and economic self-sufficiency initiatives. The adoption of iPads and digital media enhances instructional effectiveness and institutional visibility, while structured religious programs preserve the pesantren’s spiritual foundation. Community involvement and alumni networks contribute to institutional sustainability and reputation, and entrepreneurial activities support financial independence. These integrated strategies demonstrate how pesantren can adapt to modern educational demands without compromising their religious identity. The study contributes to understanding strategic management practices in Islamic boarding schools facing increasing educational competition.